Back on Track: Wyomia Tyus, Breaking Historical Silences, and the Sporting Activist Legacies of 1968. Issue 9 (3rd July 2019) - Liberti, Rita; McDonald, Mary G.
Abstract: After her Olympic gold medal winning performance (her third over two Olympiads) as a member of the 4 × 100 metre relay team in 1968, US sprinter Wyomia Tyus dedicated the victory to fellow track athletes Tommie Smith and John Carlos. This dedication occurred in the midst of the controversy generated by Smith and Carolos's protest against racial injustice at the Games. In that emotionally charged moment, Tyus stood in defense of her teammates and the larger project for human rights, this despite being largely ignored by the movement up until that point. Unfortunately, disregard for Tyus and her actions continued, with few taking notice of her political stances. Drawing upon her recently published memoir, Tigerbelle: The Wyomia Tyus Story and related documents produced since 1968, this paper reengages and reconsiders Tyus' actions in the broader context of African American women's activisms in the late 1960s and beyond. This paper demonstrates the ways in which Tyus and others have 'talked back' against these historically created omissions. By interjecting her views over the course of time, Tyus has produced a rich archive suggesting the failure of hegemonic efforts to completely silence her resistive efforts in challenging racial and gendered lines of power.